Determination of the service life of deflecting drums of belt conveyors - Balabaev, Оюм; Kulzhabaeva, Айгул; Taishubekova, Айгул; Rakhimov, Арман (Рroblems of engineering and professional education, 2023)
The article deals with the results of determination of service life of deflection drums of ore belt conveyors. The maximum capacity of the deflection drum shells is determined by the ANSYS research results. The work carried out will expand the calculation bases of the powerful structure and extended conveyors, as well as for mining industries.